eCM 2017
DOI: 10.22203/ecm.v033a19
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extracellular acidosis on the behaviour of mesenchymal stem cells in vitro

Abstract: The stem cell fraction of a cell population is finely tuned by stimuli from the external microenvironment. Among these stimuli, a decrease of extracellular pH (pHe) may occur in a variety of physiological and pathological conditions, including hypoxia and inflammation. In this study, by using bone marrow stem cells and dental pulp stem cells, we provided evidence that extracellular acidosis endows the maintenance of stemness in mesenchymal cells. Indeed, continuous exposure for 21 d to low pHe (6.5-6.8) condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 23 publications
3
32
0
Order By: Relevance
“…By itself, the acidic milieu favors the dissolution of bone matrix [11], but, also, it may alter some cell functions involved in the mineralization process. In agreement with literature data, we found that pH 6.9 decreases ALPL and Runx2 expression [57], induces a slight increase in OPG, while collagen and BGLAP were not affected [5,58,59]. Alkaline phosphatase plays a pivotal role in regulating bone mineralization, since it catalyzes the inorganic pyrophosphate (PPi) hydrolysis and provides inorganic phosphate (Pi) for the nucleation of hydroxyapatite crystals [60].…”
Section: Discussionsupporting
confidence: 85%
“…By itself, the acidic milieu favors the dissolution of bone matrix [11], but, also, it may alter some cell functions involved in the mineralization process. In agreement with literature data, we found that pH 6.9 decreases ALPL and Runx2 expression [57], induces a slight increase in OPG, while collagen and BGLAP were not affected [5,58,59]. Alkaline phosphatase plays a pivotal role in regulating bone mineralization, since it catalyzes the inorganic pyrophosphate (PPi) hydrolysis and provides inorganic phosphate (Pi) for the nucleation of hydroxyapatite crystals [60].…”
Section: Discussionsupporting
confidence: 85%
“…Although less detrimental than glucose shortage, lower intracellular and extracellular pH levels inhibit MSC metabolism, proliferation, and osteogenic differentiation. [77][78][79][80][81][82][83] Acidifying the extracellular medium of rabbit MSCs to pH 6.8-7.0 resulted in large decreases in the glucose consumption rate and the lactate production rate (48.3% and 95.1%, respectively), compared with standard cell culture conditions at pH >7.4. 78 This finding suggests a reduction in glycolysis, which may be a feedback system to avoid further acidification of the extracellular space that would ultimately lead to an excessive acidification of the cytosol and cell death.…”
Section: Effects Of Phmentioning
confidence: 99%
“…78 This finding suggests a reduction in glycolysis, which may be a feedback system to avoid further acidification of the extracellular space that would ultimately lead to an excessive acidification of the cytosol and cell death. 77,78 Moreover, Massa et al 81 Consequently, research should refocus its effort to rationally engineer a new generation of cell-containing scaffolds that provide nutrients tailored to the needs of transplanted cells. Given that glucose (and not oxygen) is essential to ensure MSC survival via glycolysis, 29,30,57 recent strategies have focused on delivering this chemical compound to cells.…”
Section: Effects Of Phmentioning
confidence: 99%
“…Moreover, several studies report that subsequently to MSC recruitment, tumor tissues educate MSCs to adopt a tumor-growth promoting phenotype [13]. In response to tumor derived acidity, resident MSCs are reprogrammed to tumor tissue-derived MSCs (t-MSCs), which further increase local acidification sustaining tumor progression [14,15]. Several studies demonstrated that MSCs induce pro-proliferative effects on tumor cells, promote OS stemness and epithelial to mesenchymal transition (EMT), recruit immunosuppressive cells and support tumor angiogenesis [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MSCs-stimulated OS cells increase the expression of pro-angiogenetic factors and promote migration, invasion and formation of the capillary network of endothelial cells in vitro [18]. Moreover, between MSCs and sarcoma cells a strict cross-talk is established: really, local tumor-derived acidosis, as well as, tumor associated osteolysis exert a great impact on MSC stemness [14,15]. Also lactate, the main driver of tumor acidosis, has a key role in OS progression: Bonucelli G. et al demonstrated that MSCs are induced by adjacent OS cells to undergo Warburg metabolism and hence to increase lactate production and monocarboxylate transporter 4 (MCT4) expression.…”
Section: Introductionmentioning
confidence: 99%